CD62Ldim Neutrophils Specifically Migrate to the Lung and Participate in the Formation of the Pre-Metastatic Niche of Breast Cancer - Wang, Zhen; Yang, Chenghui; Li, Lili; Zhang, Zhigang; Pan, Jun; Su, Ke; Chen, Wuzhen; Li, Jinfan; Qiu, Fuming; Huang, Jian (Frontiers in Oncology, 2020)
Lung metastasis is one of the leading causes of death in patients with breast cancer. The mechanism of tumor metastasis remains controversial. Recently, the formation of a pre-metastatic niche has been considered a key factor contributing to breast cancer metastasis, which might also explain the tendency of organ metastasis. Our study initially re-examined the critical time of the niche formation and simultaneously detected a novel subset of neutrophils, CD62Ldim neutrophils, which had not previously been reported in tumor metastasis; the number of these cells progressively increased during breast cancer progression and was closely related to the formation of the pre-metastatic niche. Furthermore, we explored the mechanism of their aggregation in the pre-metastatic niche in the lung and found that they were specifically chemoattracted by the CXCL12-CXCR4 signaling pathway. Compared to the CD62Lhi neutrophils, CD62Ldim neutrophils exhibited stronger adhesion and increased survival. The results provide new insights into the subsequent targeted treatment of breast cancer metastasis.